A lesson learned by attending 37 years of loss prevention symposia. Issue 1 (27th November 2015) - Pratt, Thomas H.
Abstract : In responding to the request to give a paper at the 50th Loss Prevention Symposium, this article gives a brief synopsis of my career, and how attending the annual LPS meetings over the last 37 years has tremendously supported my professional work. It relates how a theoretical physical chemist was transformed into a consultant having an expertise in electrostatic ignitions of fires and explosions. Of all the reasons, one could have for attending an LPS, networking is singled out, emphasized, and supported by examples. © 2015 American Institute of Chemical Engineers Process Saf Prog 35: 5–7, 2016